Comparison between ANSYS and CATIA simulation capability in simulating round shape diaphragm of MEMS piezoresistive pressure sensor - Zaiazmin, Y. N.; Ishak, Abdul Azid (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org